Determinants Factors Affecting Quality of Financial Statement Information: External Factors as Moderating Variables - Mohammad Syafik; Doddy Setiawan (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2023)
AbstractThe purpose of this research is to provide knowledge related to the influence of the internal control system, the use of information technology and human resource capacity on the quality of financial statement information with external factors as moderating variables. The questionnaire used to gather the data for this study was distributed to 107 Lamongan district employees who work in the financial industry. This research proves that the internal control system, utilization of information technology and human resource capacity has a positive and significant impact on the quality of financial statement information. external factors have no influence on the capacity of human resources on the quality of financial statement information. Future studies may select a wider sample, such as the Provincial Government.Keywords:Internal control system, utilization of information technology, human resource capacity and quality of financial report information.